ESTIMATION OF RENEWABLE ENERGY SOURCES APPLICATION IN THE SYNERGY WITH EUROPEAN UNION POLICY - G. Kharlamova (Vìsnik. Kiïvsʹkogo Nacìonalʹnogo Unìversitetu ìmenì Tarasa Ševčenka. Ekonomìka, 2018)

(untitled)
This paper gives the possibility to analyze the application of renewable energy sources (RES) at different stages of their implementation to energy supply. Through the world experience we research the dynamics of energy consumption by its types; determine, what kinds of alternative sources are demanded most of all. In addition, we assess the efficiency of the application of RES in Ukraine. According to statistical and correlation analysis, it was proved that for Ukraine it is the most profitable to use biomass energy, while solar energy remains relatively expensive for our country. At the same time situation may change if costs for the solar panel will decrease in the future. It is shown that use of alternative energy sources decrease the energy intensity of GDP, while fossil resources increase this parameter. Unfortunately, Ukraine faces difficulties in attracting investments for development of RES as they are not so profitable at this time. It means that government should change its policy, increasing electricity prices to the European level, giving the chance for energy independence. In any case, in Ukraine, it will be necessary to increase the introduction of RES, as our country has only about 2% of RES in energy balance, while European countries in average have 17% and some of them have more than 60%.